The Drosophila TRPA channel, Painless, regulates sexual receptivity in virgin females. - Sakai, T.; Kasuya, J.; Kitamoto, T.; Aigaki, T. (Genes, Brain, and Behavior, 2009)
Transient receptor potential (TRP) channels play crucial roles in sensory perception. Expression of the Drosophila painless (pain) gene, a homolog of the mammalian TRPA1/ANKTM1 gene, in the peripheral nervous system is required for avoidance behavior of noxious heat or wasabi. In this study, we report a novel role of the Pain TRP channel expressed in the nervous system in the sexual receptivity in Drosophila virgin females. Compared with wild-type females, pain mutant females copulated with wild-type males significantly earlier. Wild-type males showed comparable courtship latency and courtship index toward wild-type and pain mutant females. Therefore, the early copulation observed in wild-type male and pain mutant female pairs is the result of enhanced sexual receptivity in pain mutant females. Involvement of pain in enhanced female sexual receptivity was confirmed by rescue experiments in which expression of a pain transgene in a pain mutant background restored the female sexual receptivity to the wild-type level. Targeted expression of pain RNA interference (RNAi) in putative cholinergic or GABAergic neurons phenocopied the mutant phenotype of pain females. However, target expression of pain RNAi in dopaminergic neurons did not affect female sexual receptivity. In addition, conditional suppression of neurotransmission in putative GABAergic neurons resulted in a similar enhanced sexual receptivity. Our results suggest that Pain TRP channels expressed in cholinergic and/or GABAergic neurons are involved in female sexual receptivity.